1994
DOI: 10.1159/000239167
|View full text |Cite
|
Sign up to set email alerts
|

Postantibiotic Effect, and Postantibiotic Effect of Subinhibitory Concentrations, of Sparfloxacin on Gram-Negative Bacteria

Abstract: The postantibiotic effect (PAE), the postantibiotic sub-MIC effect (PA SME), and the sub-MIC effect (SME) of a new oral quinolone, sparfloxacin, were determined for different strains of gram-negative bacteria. A PAE was induced by 10 x MIC of sparfloxacin for 2 h and the antibiotic was then eliminated by washing and dilution. The PA SME was studied by adding different sub-MICs during the postantibiotic phase, and the SME by exposing the controls to the sub-MICs alone. Growth curves were followed for 20 h by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…A number of in vitro studies have quantified the PAE induced by numerous antibiotics in a variety of Gram-positive 10,19,20,21,23,30 and Gram-negative bacteria 19,20,21,32 .…”
Section: Discussionmentioning
confidence: 99%
“…A number of in vitro studies have quantified the PAE induced by numerous antibiotics in a variety of Gram-positive 10,19,20,21,23,30 and Gram-negative bacteria 19,20,21,32 .…”
Section: Discussionmentioning
confidence: 99%
“…The PAEs of different quinolones have also been confirmed by different authors (1, 12-14, 18, 19), but the duration was always shorter than those observed if aminoglycosides were used. Odenholt-Tornquist & Bengtsson (12) checked the PAEs of sparfloxacin against different Gram-negative clinical isolates by using the drug at 1OX MIC concentration. The PAE found was 1 h against P. aeruginosa isolates (12).…”
Section: Discussionmentioning
confidence: 99%
“…When we use antibiotics with a long half-life, such as 4-fluoroquinolones, part of the delay attributed to the PAE could be due to this action of residual concentrations in the tissue [4], Great in vitro bactericidal actions of the three antibiotics against the two microorgan isms have been observed (table 2). There are several studies on quinolones: sparfloxacin [31,32], that induced long PA-SEs but small SEs against Staphylococcus pyogenes and gram-negative bacteria, and with ciprofloxa cin, Zhanel et al [33] have studied the PAE and the SE of 1/2, 1/4 and 1/8 x MIC against Pseudomonas aeruginosa, and they found that they produced a growth inhibition for several hours.…”
Section: Discussionmentioning
confidence: 99%